Towards a healthy progression - New Straits Times, Najuah Ismail (2010)
Thomas Edison got it partially right when he said that "the doctor of the future will give no medicine but will interest his patients in the care of the human frame, in diet and in the cause and prevention of disease." While administering medicine is still a practice in the treatment of patients, health sciences has developed into a multi-disciplinary field that is concern not only with the treatment of diseases but also the improvement and advancement of all aspects of wellness and health care.